Stability and order in Europe revisited: lessons since 1945 - Mohd Noor Yazid (Penerbit Universiti Kebangsaan Malaysia, 2023)
This paper revisits the question of the international structure and political stability in Europe before and after 1945. It is argued that there were relations between the international political system and political stability in Europe during the two periods: the period from 1900 to 1945 and from 1945 to 1989. Instructive lessons from global political history and Mearsheimer's Neorealism have shown the instability of multipolarity in the present decline of the US order. This is because the international political structure strongly influenced the degree of stability in Europe. The different global political structure affected the different levels of stability before and after 1945. The bipolar structure strongly influenced and determined Europe's power configuration and stability after 1945. The instability of Europe before 1945 was strongly related to the multipolarity structure; there were many great powers, and the existence of multiple polarities with seven great powers posed difficulty in managing them. Thus, striking a balance between them was nearly impossible and was a lesson for today's reading of international politics.